The lost apothecary [large type] - Penner, Sarah (Thorndike Press large print core, 2021)
Hidden in the depths of eighteenth-century London, a secret apothecary shop caters to an unusual kind of clientele. Women across the city whisper of a mysterious figure named Nella who sells well-disguised poisons to use against the oppressive men in their lives. But the apothecary's fate is jeopardized when her newest patron makes a fatal mistake, sparking a string of consequences that echo through the centuries. Meanwhile in present-day London, aspiring historian Caroline Parcewell stumbles upon a clue to the unsolved apothecary murders that haunted London two hundred years ago, her life collides with the apothecary's--and not everyone will survive.